2015
DOI: 10.3109/0142159x.2015.1031734
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of high-fidelity simulation versus lecture-based education in preclinical medical students

Abstract: High-fidelity simulation may serve as a viable didactic platform for preclinical medical education. Our study demonstrated equivalent immediate knowledge gain and superior long-term knowledge retention in comparison to lectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 24 publications
5
45
1
1
Order By: Relevance
“…Several studies have demonstrated the equivalence or superiority of HFS as an educational technique to learning enhancement and knowledge retention of a taught topic (1,13). The results from our study are compatible with these results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated the equivalence or superiority of HFS as an educational technique to learning enhancement and knowledge retention of a taught topic (1,13). The results from our study are compatible with these results.…”
Section: Discussionmentioning
confidence: 99%
“…The preclinical core of medical education has traditionally been based on lectures and textbooks (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the sample size was small and a significant number of study subjects dropped out prior to the 1-year assessment, the study suggests that the efficacy of simulation-based training was maintained over 1 year; meanwhile, the water-drills group showed diminished performance with time. A previous study also reported 1-day simulation training can increase knowledge and contribute to the maintenance of knowledge over time (11,12). Vadnais et al (11) reported that further benefit was gained by repeat exposure to simulation training.…”
mentioning
confidence: 96%